2021
DOI: 10.3390/cancers13236066
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study on the Molecular Profiling of Primary Melanomas Reveals a Progression Dependence on Mitochondrial Activation

Abstract: Melanoma in advanced stages is one of the most aggressive tumors and the deadliest of skin cancers. To date, the histopathological staging focuses on tumor thickness, and clinical staging is a major estimate of the clinical behavior of primary melanoma. Here we report on an observational study with in-depth molecular profiling at the protein level including post-translational modifications (PTMs) on eleven primary tumors from melanoma patients. Global proteomics, phosphoproteomics, and acetylomics were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…Mitoribosomes were earlier proposed and used as potential targets for anticancer therapies (Kim et al, 2017; Lamb et al, 2015; Škrtić et al, 2011). Recently, in an observational study on primary melanomas, mitochondrial translation upregulation was discovered in the disease recurrence group (Gil et al, 2021). In the present study, we observed positive correlations between the levels of mitoribosomes and the proliferation status of the tumors at both protein and transcript levels, as previously reported (Akbani et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitoribosomes were earlier proposed and used as potential targets for anticancer therapies (Kim et al, 2017; Lamb et al, 2015; Škrtić et al, 2011). Recently, in an observational study on primary melanomas, mitochondrial translation upregulation was discovered in the disease recurrence group (Gil et al, 2021). In the present study, we observed positive correlations between the levels of mitoribosomes and the proliferation status of the tumors at both protein and transcript levels, as previously reported (Akbani et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Mitoribosomes were earlier proposed and used as potential targets for anticancer therapies (Kim et al, 2017;Lamb et al, 2015;Škrtić et al, 2011). Recently, in an observational study on primary melanomas, mitochondrial translation upregulation was discovered in the disease recurrence group (Gil et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While our study cohort for nonrecurrent melanoma consisted exclusively of male, it is important to note that the identified risk factors for recurrence, characterized by downregulated immune response pathways, are considered gender-independent markers of recurrence risk. 4 Among the 166 significantly dysregulated proteins between tumour cell groups, a cluster of proteins involved in collagen formation, complement and coagulation cascades and immune response activities stood out with the highest score (Figure 4B). Additional immune response markers like CD1A were downregulated in recurrent cases.…”
Section: E T T E R T O T H E J O U R N a L Mitochondrial And Immune R...mentioning
confidence: 99%
“…Building upon our foundational work in the Human Melanoma Proteome Atlas, which extensively characterized melanoma presentations and molecular pathology, this study represents a significant advancement. [2][3][4] We now focus on a more targeted approach, isolating specific tumour regions to intricately investigate the interplay between tumour cells and the stromal component. This progression in our research strategy deepens our molecular understanding of the tumour microenvironment's significance in melanoma recurrence.…”
Section: E T T E R T O T H E J O U R N a L Mitochondrial And Immune R...mentioning
confidence: 99%